An An Analysis of Language Variation in Banjar Puaya: A Sociolinguistic Study - Widiasmara, I Komang (Universitas Kapuas, 2023)
Language and society have strong relations on each other in which they interfere on any aspect in a language. Social interaction can emerge large variety of languages because the speakers may produce new languages more and have more choices in using the language. This case can be referred to language varieties that occur within a social interaction. This study was aimed to analyze the language variations in Banjar Puaya communities. The research used a qualitative method with a case study to explain the phenomenon found in the field. The data analysis was done by observing and interviewing youth and adult communities of Banjar Puaya. The result found some classifications of language variations namely dialects, registers, mixtures of varieties, and secret language variations. The variation occurred based on the environment and situation and condition's influence. Therefore, it is possible that language can still be modified and developed since the society makes any variation in the use of language.